Dynamic change of bacterial diversity, metabolic pathways, and flavor during ripening of the Chinese fermented sausage - Wang, Ji; Aziz, Tariq; Bai, Ruxue; Zhang, Xin; Shahzad, Muhammad; Sameeh, Manal Y.; Khan, Ayaz Ali; Dablool, Anas S.; Zhu, Yingchun (Frontiers in Microbiology, 2022)
Chinese fermented sausage is a famous, fermented meat product harboring complex microbial flora with potential impact on flavor and quality. The aim of the present study was to explore bacterial diversity, metabolic pathways, and changes in flavor compounds during the ripening of fermented sausages using Lactobacillus plantarum MSZ2 and Staphylococcus xylosus YCC3 as starter culture. Bacterial community structure, volatile flavor compounds and metabolic pathways were assessed in the fermented sausage samples on day 0, 6 and 12 using advanced next generation sequencing and Headspace Solid-phase microextraction-gas chromatography-mass spectrometry. Lactobacillus, Staphylococcus, Lactococcus, Leuconostoc and Weissella were the most abundant bacterial genera found in the sausage samples during at all stages of fermentation. Functional prediction reveals abundance of 12 different metabolic pathways, the commonest being carbohydrates, amino acids, and nucleotides metabolism. A total of 63 volatile compounds were also identified in fermented sausage samples. Correlational analysis showed that Staphylococcus and Leuconostoc were closely related to flavor compounds. Results of the study may provide guidance for industrial production of fermented sausages utilizing microbiota for improved flavor, quality, and preservation.